INDICATORS AND BIOINDICATORS OF WATER QUALITY IN ARTIFICIAL WETLANDS: CASE STUDY IN CENTRO, TABASCO - López Ocaña, Gaspar; Calderón Miranda, Marilyn; Campos Campos, Bernardita; Pérez de la Cruz, Manuel (Kuxulkab', 2024)
The DACBiol-UJAT has a sump-tank and two trains (T1 and T2) with three wetlands in series of subsurface flow with “Potenderia cordata”, free flow with “Thalia geniculata” and a second free flow with “Sagittaria lancifolia”. The COD removal efficiency in both trains was 98 %. “S. lancifolia” showed better performance in T1 and “T. geniculata” in T2. The three species are easy to maintain and efficient in removing basic contaminants and wetlands with “S. lancifolia”  present the greatest number of organisms that are considered bioindicators in artificial wetlands.
Keywords: Wastewater; Macrophytes; Chemical oxygen demand; Removal efficiency; Environmental compliance